Corrosion of carbon steel in the presence of oilfield deposit and thiosulphate-reducing bacteria in CO2 environment - Machuca Suarez, Laura; Lepkova, Katerina; Petroski, A. (Elsevier, 2017)
The effect of thiosulphate reducing bacteria (TRB) on the corrosion of carbon steel covered by a complex oilfield deposit has been assessed in CO 2 -containing seawater at 55 Â°C. TRB were found to significantly accelerate localized corrosion at deposited steels. This effect of TRB on under-deposit corrosion (UDC) was related to metabolic production of corrosive compounds, such as sulphide and acidic species, through biodegradation of organic matter and thiosulphate reduction in the deposit. TRB were also found to promote accumulation of hydrocarbons and metals in the deposit. Results highlight that microbial-deposit interactions are a noteworthy process in corrosion of oilfield facilities.